Research governance in academia : are there alternatives to academic rankings? - Margit Osterloh; Bruno S. Frey (Center for Economic Studies and ifo Institute (CESifo), 2009)
Peer reviews and rankings today are the backbone of research governance, but recently came under scrutiny. They take explicitly or implicitly agency theory as a theoretical basis. The emerging psychological economics opens a new perspective. As scholarly research is a mainly curiosity driven endeavor, we include intrinsic motivation and supportive feedback by the peers as important determinants of scholarly behavior. We discuss whether a stronger emphasis on selection and socialization offers an alternative to the present regime of academic rankings.
Keywords: O00; 330; peer reviews; rankings; research governance; agency theory; psychological economics; new public management; economics of science; control theory; Hochschulforschung; Bewertung; Publikationsanalyse; Wissenschaftspolitik; Governance-Ansatz; Wirtschaftspsychologie; Agency Theory